Rheological behavior of Al2O3/R141b nanorefrigerant - Mahbubul, I.M.; Khaleduzzaman, S.S.; Saidur, R.; Amalina, M.A. (Elsevier, 2014)
Nanorefrigerants are potential nanofluid that can improve the performance of refrigeration and air-conditioning system. Rheological properties of these fluids need to analyze before practical implementation as they influence the flow characteristics. In the present work, the rheological behavior (relation of shear stress and viscosity with shear rate) of Al2O 3/R141b nanorefrigerant for 0.05-0.15 volume concentrations with the temperature ranging from 4 to 16 C was studied. From this experiment, it is found that, the nanorefrigerant showed non-Newtonian and shear thickening behavior. However, at high shear rates, the trend was found to be quite close to Newtonian behavior. Moreover, viscosity increases with the increase of shear rates and volume concentrations, however, decreases with the increase of temperature. Â© 2014 Elsevier Ltd. All rights reserved.